Tumor Microenvironmental Signaling Elicits Epithelial-Mesenchymal Plasticity through Cooperation with Transforming Genetic Events - Damian J. Junk (Neoplasia: An International Journal for Oncology Research, 2013)
Epithelial-to-mesenchymal transition (EMT) facilitates the escape of epithelial cancer cells from the primary tumor site, which is a key event early in metastasis. Here, we explore how extrinsic, tumor microenvironmental cytokines cooperate with intrinsic, genetic changes to promote EMT in human mammary epithelial cells (HMECs). Viral transduction of transforming genetic events into HMECs routinely generated two distinct cell populations. One population retained epithelial characteristics, while an emergent population spontaneously acquired a mesenchymal morphology and properties associated with cancer stem cells (CSCs). Interestingly, the spontaneous mesenchymal/CSCs were unable to differentiate and lacked epithelial-mesenchymal plasticity. In contrast, exposure of the transformed HMECs retaining epithelial characteristics to exogenous transforming growth factor-β (TGF-β) generated a mesenchymal/CSC population with remarkable plasticity. The TGF-β-induced mesenchymal/CSC population was dependent on the continued presence of TGF-β. Removal of TGF-β or pharmacologic or genetic inhibition of TGF-β/SMAD signaling led to the reversion of mesenchymal/CSC to epithelial/non-CSC. Our results demonstrate that targeting exogenous cytokine signaling disrupts epithelial-mesenchymal plasticity and may be an effective strategy to inhibit the emergence of circulating tumor cells. The model of epithelial-mesenchymal plasticity we describe here can be used to identify novel tumor microenvironmental factors and downstream signaling that cooperate with intrinsic genetic changes to drive metastasis. Understanding the interaction between extrinsic and intrinsic factors that regulate epithelial-mesenchymal plasticity will allow the development of new therapies that target tumor microenvironmental signals to reduce metastasis.